Improving Students’ Pronunciation Accuracy through Shadowing Technique combined with minimal pairs in An English Pronunciation Class - Muman Muman; Hendra Husnussalam (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
This study investigated how students’ English pronunciation skills improved through the implementation of the shadowing technique combined with minimal pairs practice. The study aimed to address students’ pronunciation problems, specifically errors in vowel and consonant articulation and inconsistent intonation patterns, which hindered their fluency and intelligibility. The participants were 37 students enrolled in the Pronunciation course of the English Education Study Program at IKIP Siliwangi during the even semester of the 2024/2025 academic year. The research followed two action research cycles, each involving the stages of planning, action, observation, and reflection. Data were collected through pronunciation pre-tests, cycle assessments, post-tests, classroom observations, and reflective journals. Quantitative data were analyzed by comparing the average pronunciation scores across the stages, while qualitative data were used to describe behavioral and attitudinal changes. The findings revealed a significant improvement in students’ pronunciation performance, with the average score increasing from 46.1 in the pre-test to 75.6 in Cycle 1 and 82.8 in Cycle 2. Students demonstrated greater accuracy in producing segmental sounds and showed more natural rhythm and intonation patterns in spoken tasks. The integration of shadowing and minimal pairs proved effective in enhancing both fluency and accuracy. These results imply that incorporating systematically structured and interactive pronunciation activities into English language instruction can provide a practical and effective approach for addressing learners’ segmental and suprasegmental difficulties, ultimately supporting more intelligible and confident oral communication.